Lithuania's electors: Reasons behind party choice - Degutis, Mindaugas (Politologija, 1997)
It is argued in the article that the behavior of the electors exposed a great deal of sensations to both political scientists and sociologists. Unexpected victory of the Democratic Labour Party in the elections of 1992 articulated analogous unexpectedness four years later, in 1996. These results were explained similarly: the electors are disappointed with the activities of the government and so chose the oppositionary power.This proposition reveals just a part of the truth because each government which governs at some particular hard time is destined to some smaller or bigger condemnation. But that was an inexhaustive and insufficient base for the explanation of the entire electoral behavior. The so-called principle of a pendulum proves insufficiency here as well. First, there was no pendulum between the Labour and the Conservative parties; second, this pattern tells nothing about the so-called third powers, which gain gradual significance.It becomes obvious that Lithuania's electors are neither those to rush leftwards/rightwards at a choice nor the ones to form two permanent groups (if one does not attend the elections, the other celebrates the victory). The author provides us with an insight into the behavior of the electors at a micro level. The article might be named a provision of empirical material where both theoretical innovations and reasonable interpretations appear to be absent.This article is based upon several questions given to 1200 respondents had 1996 Seimas Elections passed. Some comments and parallels are present, however, this is not the main aim of the article: the study observes but does not interpret.
Keywords: -